"OVARIAN DISEASES IN WOMEN AND OVARIAN CANCER" (Western European Journal of Medicine and Medical Science, 2024)
Macroscopically, ovarian tumors are presented in the form of cystic formations filled with fluid, or in the form of a dense node, reaching various sizes. It is currently believed that all ovarian neoplasms develop from a single tissue component.